Pengaruh Kualitas Produk, Harga, Kualitas Pelayanan, Dan Store Atmosphere Terhadap Kepuasan Pelanggan - Devina Martina Lieyanto; Bruno Hami Pahar (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
The development of culinary business in Indonesia, particularly in Surabaya, is growing and developing increasingly. Gatherinc Bistro & Bakery is one of the bistros in Surabaya and is located on Jalan Taman Puspa Raya A2 No. 11, Sambikerep, Surabaya. The aim of this study is to determine the effect of quality of product, price, quality of service, and store atmosphere on customer satisfaction at Gatherinc Bistro & Bakery Surabaya. The method used in this study is quantitative research by giving a questionnaire statement to 100 participants who are customers of Gatherinc Bistro & Bakery Surabaya. This research was tested using the Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), F Test, Multiple Linear Regression Test, Determinant Coefficient, and t test. In the t test, the research results showed that the variable quality of the product (X1) 1.648 < 1.985 with a significant level of 0.103 > 0.050, which means that quality of product has no significant effect on customer satisfaction at Gatherinc Bistro & Bakery Surabaya, variable price (X2) 0.176 < 1.985 with a significant level of 0.861 > 0.050, which means that price does not have a significant effect on customer satisfaction at Gatherinc Bistro & Bakery Surabaya, quality of service (X3) 3.755 > 1.985 with a significant level of 0.000 < 0.050, which means that quality of service has a significant effect on customer satisfaction at Gatherinc Bistro & Bakery Surabaya, and the store atmosphere (X4) 2.280 > 1.985 with a significant level of 0.025 < 0.050, which means that store atmosphere has a significant effect on customer satisfaction at Gatherinc Bistro & Bakery Surabaya. The conclusion of this study is that the product and price quality variables do not have a major impact on customer satisfaction because the quality of products and prices given by Gatherinc Bistro & Bakery Surabaya are not much different from other cafe or bistro in Surabaya, whereas the service quality and store environment variables at Gatherinc Bistro & Bakery Surabaya have an impact on customer satisfaction.